The tale of troy - Green, Roger Lancelyn; Baynes, Pauline (Puffin Books London, 1994)
The Tale of Troy tells the last great adventure of the Heroic Age. It is the story of Helen and the judgment of Paris; of the gathering of the heroes and the siege of Troy; of Achilles, reared by the Centaur on wild honey and the marrow of lions; of Odysseus and the great strategy of the first Wooden Horse, and of his many adventures on his long journey home to Greece